Nexus solutions for water productivity and food security - Lankford, B.A.; Koirala, Sanju; Amarasinghe, Upali A.; Mabhaudhi, Tafadzwanashe (CGIAR System Organization, 2023)
On 16 October, scientists, politicians and world leaders gathered from around the world to celebrate World Food Day. Organized by the Food and Agriculture Organization of the United Nations, the annual event urged global action to ‘start managing water wisely’ in the race for zero hunger. Stressing the connections between water and food production, this year’s World Food Day served as an important reminder that food and nutrition security can only be achieved with sufficient water of adequate quality, quantity, and reliability.